Efecto de la aplicación de sulfato de potasio al racimo en Palma Aceitera (Eleais guinensis. Jacq), sobre la producción de aceite - Vargas Martínez, Dalember Wilmer (2017)
VIII. SUMMARY The present experimental work was carried out in Km. 17 ½ of the Babahoyo - Montalvo road with an altitude of 70 meters above sea level. The zone presents a humid tropical climate, with an average temperature of 25,50 ˚C, annual rainfall of 2,329 mm, relative humidity of 82 % and 987,10 hours of annual average heliophany. The soil presents flat topography, loamy clay texture, without irrigation system and drainage by channels. During the development of the experimental work the following materials were used: stick, paper covers, knives, chopping board, cotton, absorbent paper, porcelain capsule, Roman, balance, machete, bucket, among others. The equipment was stove and backpack pump. The sowing material used was the 8-year-old Deli x Ghana hybrid with planting distance of 9 x 9 x 9 m between plants distributed in the form of three bolillos, providing a planting density of 143 plants / ha. The orientation of the rows of palms are North-South. The treatments under study were potassium sulphate doses of 0,70; 1,40; 2,10 and 2,90 kg / ha of the product, plus an absolute control without application. The design of Random Blocks was used, with five treatments and three repetitions. The comparison of the averages was made with the Tukey statistical test at 95 % probability. During the development of the trial, irrigation, fertilization, phytosanitary controls, weed control and harvesting were carried out. The data evaluated were bunch weight and fruit; width and length of the fruit; moisture of the mesocarp in fresh and dry; moisture of the seed in fresh and dry; number of fertile fruits; number of white fruits; number of paternalcarpal fruits; percentage of oil extraction; performance and economic analysis. The conclusions determined that the application of potassium sulfate to the cluster helped to increase the production of oil in the cultivation of Palma Aceitera (Eleais guinensis, Jacq), in the area of Montalvo - Los Ríos; the variables weight of the bunch and of the fruit, width and length of the fruit registered higher averages with the use of 0,70 kg / ha of potassium sulfate; the highest humidity of the mesocarp in fresh corresponded to the use of 1,40 kg / ha of potassium sulphate, while in dry it was for the dose of 0,70 kg / ha of the product; the humidity of the seed in fresh, the values stood out using 0,70 kg / ha, whereas in dry it was for the dose of 2,10 kg / ha of potassium sulfate; the greatest number of fertile fruits was obtained by the treatment that was applied 0,70 kg / ha of potassium sulphate and in the number of infertile fruits was for the use of 2,90 kg / ha of the product; the highest number of white fruits and paternalcarp was observed in the treatment that was used 2,90 kg / ha of potassium sulfate and the percentage of oil extraction, yield and economic analysis exceeded the results in the treatment that was applied potassium sulfate in doses of 0,70 kg / ha.